Pengaruh Kepercayaan Diri, Integritas dan TI Terhadap Kecurangan Akademik Mahasiswa - Veronika Pude Lengari; Uum Helmina Chaerunisak (Yayasan Literasi Ilmiah Indonesia, 2025)
Purpose: This Study aims ti determine (1) To prove whether self-confidence affects academic cheating behavior (2) To prove whether student integrity affects academic cheating behavior (3) To prove whether misuse of information technology affects academic cheating behavior (4) To prove whether learning motivation can strengthen the effect of self-confidence on academic cheating behavior (5) To prove whether learning motivation can strengthen the effect of student integrity on academic cheating behavior (6) To prove whether learning motivation can strengthen the effect of misuse of information technology on academic cheating behavior. Method: This research uses a quantitative approach. The data used is primary data with data collection methods through distributing questionnaires online using Google Form. The population in this study were accounting students at various universities in Indonesia. The sample obtained was 373 samples. The sampling technique used snowball sampling with the data analysis method in the form of multiple linear regression methods with SPSS 25 software. Finding: Based on the results of the study, it shows that self-confidence has no significant effect on academic fraud behavior, student integrity has a negative and insignificant effect on academic fraud behavior, misuse of information technology has a positive and significant effect on academic fraud behavior, learning motivation strengthens the relationship between self-confidence and academic fraud behavior, learning motivation strengthens the relationship between student integrity and academic fraud behavior, learning motivation strengthens the relationship between technology misuse and academic fraud behavior, Novelty: This study adds the variable of self-confidence, as a factor influencing academic cheating behavior, adding the variable of learning motivation as a moderating variable that has not been examined in previous studies.